Comércio e protecionismo em bens intermediários - Flavio Lyrio Carneiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This study analyses the tariff protection structure that Brazil imposes on intermediate goods, examining its recent development and comparing it with that of selected developing countries, in order to assess whether or not Brazilian protection on this type of products is more restrictive than in other countries. Both the aggregate data and the various breakdowns adopted lead to the conclusion that Brazilian tariffs on intermediate goods are, in general, considerably higher than those of the other countries examined. Furthermore, for most countries, it is possible to distinguish a clear downward trend in these tariffs, while in Brazil, at the end of the period analysed, tariffs on intermediates increased both in aggregate disaggregated data (that is, in all technological intensity categories, sections and chapters). However, the analysis suggests that, with few exceptions, Brazilian tariffs on intermediate goods are generally lower than the aggregate average tariff that includes all use categories. This fact indicates that the high protection imposed on intermediate goods follows directly from high tariff protection structure imposed on imports as a whole, rather than any bias in the tariff structure towards this type of good. Still, the excessive protection imposed by Brazil on imports of intermediate goods likely to affect Brazilian international competitiveness, to the extent that it may adversely affect the cost structure of firms, since competitors in other countries can purchase inputs at a lower cost.
Keywords: F13; 330; intermediate goods; tariffs; trade policy